Higher education governance and policy: an introduction to multi-issue, multi-level and multi-actor dynamics. Issue 1 (2nd January 2017) - Chou, Meng-Hsuan; Jungblut, Jens; Ravinet, Pauline; Vukasovic, Martina
Abstract: This thematic issue introduces the multifaceted nature of contemporary public policy – its multi-level, multi-actor and multi-issue features – using the case of higher education policies from around the world. To do so, this introduction first describes how higher education as a policy sector should be garnering far more attention from scholars interested in political, economic and social transformation. A framework for identifying and accounting for how the 'multi-s' characteristics configure and re-configure public policy is then introduced. Next, this thematic issue's contributions are summarized with highlights of how they bring to life the different 'multi-s' features. This introduction concludes with a discussion of what the proposed framework of the 'multi-s' offers to studies of higher education policy coordination. In so doing, the objectives of this thematic issue are to highlight what the case of higher education policy coordination offers to studies of public policy and to initiate a dialogue between all social scientists and practitioners interested in the increased complexity of governing, producing and using knowledge today.